Dampak Persepsi Harga terhadap Minat Beli Ulang melalui Kepuasan Konsumen pada Luwak White Koffie di Kota Bandung - Amalia, Yunita Nur; Nurtiahiadi, Edi (IPM2KPE, 2024)
This study aims to explore the impact of price perception on repurchase intention through consumer satisfaction at Luwak White Koffie in Bandung City. A quantitative approach was used by collecting primary data from 120 respondents through a questionnaire. Data analysis was carried out by validity testing, reliability testing, classical assumption testing, and linear regression using SPSS version 26 software. The results showed that price perception has a positive effect on consumer satisfaction, which in turn affects repurchase intention. In addition, consumer satisfaction acts as a mediator between price perception and repurchase intention. These findings reveal the importance of paying attention to price perception and consumer satisfaction in increasing repurchase intention. Keywords: Consumer Satisfaction, Repurchase Intention, Price Perception